Social networking sites, a mechanism to achieve self-learning for university students - Derbal , Sara; Haddad , Sonia (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
Social networking sites, such as YouTube, Facebook, Instagram and other sites, have made a quantum leap in our time through the use of the Internet by modern means of communication. The world today has become very dependent on the spread and development of digital information provided by these sites, for easy access. And using it while communicating with others by all members of society at different cultural and educational levels, especially the youth group and the university student's category, because they need scientific research resources. Therefore, social networking sites today are among the modern methods that have an effective role in preparing individuals by providing them with various Customs and behaviors and their receiving of various knowledge and information, and thus it has become an important tool for social change, due to its great impact on many fields through the freedom of transfer and exchange of information between individuals, and it gives them the freedom to publish and share knowledge and information. And since the educational process that takes place through social networking sites is not just indoctrination to the learner, but is a process that allows the individual to take responsibility for his own learning through what has been termed self-learning, especially among researchers, these sites have made the learner responsible for the educational process. And the achievement of self-learning, which is a method that allows individuals in general and university students in particular the opportunity to obtain various information on their own and without assistance from others, and at a time and place that suits them.